Perbedaan lama perendaman air perasan jeruk nipis (Citrus aurantifolia Swingle) terhadap kekasaran permukaan resin komposit nanohybrid - Faustina Angela Tandrayuana; Edhie Arif Prasetyo; S. Angela Setyabudi (Universitas Airlangga, 2017)
Background: Nanohybrid Composite is a composite that is often used in dentistry because it has advantages in physical, mechanical and esthetic properties. One of the mechanical properties which can be an indicator of the resilience of restorative material is surface roughness. One of the factors that affect the surface roughness is acidic drink consumption habits. Fruit that easily processed into fresh juice and widely consumed as beverage is lime. Lime has a sour taste because it has main content of citric acid. Purpose: The aim of this study was to determine the effect of prolonged lime juice consumption to the roughness of nanohybrid composite surface. Methods: 24 composite nanohybrid samples sized 5x2 mm divided into 4 groups. The control group was immersed in sterile water, the treatment group was immersed in lime juice for 2.5 hours, 15 hours and 30 hours. Before and after immersion, all samples were tested using a Surface Roughness Tester. Data were tested statistically. Results: Kruskal Wallis Test and Tukey HSD showed significant changes in surface roughness after being immersed in lime juice. Group of 30 hours immersion obtained the greatest increase in surface roughness. Conclusion: The 30 hours immersed composite group has rougher surface than 15 hours. The 15 hours immersed composite group has rougher surface than 2,5 hours